"Aqui nem parece um hospital"...A inovação do atendimento hospitalar por meio de terapias complementares: o caso do reiki - Ya Grossi Andrade (2018)
Reiki is a practice that has an unusual method because it is an energy technique that through the imposition of hands seeks to promote the relaxation and well-being of the patient. Even so, these characteristics did not impede its institutionalization by the Ministry of Health as complementary therapy through the National Policy of Integrative and Complementary Practices (PNPIC), nor its diffusion in hospitals. However, not every hospital achieves the "success" of the service by innovating in its services through the implementation of reiki, thus, this study was carried out in one of the rare cases of successful implementation of reiki in a public hospital, that since 2012, has the full schedule of patients who are referred by health officials. In this scenario, this study opens the black box of reiki care in order to answer how the technique got to diffuse in the study hospital. The theoretical basis was based on three approaches that guided the understanding of the development of an innovation: the Network Actor Theory, the Sociotechnical approach and the Social Constructivist approach. As a general guideline for the field research, Grounded Theory (GT) and the Ergonomic Work Analysis (EWT) principles were adopted. Open, semi-structured and self-confronting interviews were conducted, as well as general and systematic observations. In addition to the reikians, health officials, patients and the hospital director were also interviewed. The results indicate that only the institutional efforts to spread the technique are not sufficient for the reiki adherence in hospitals to be effective. In this way, innovation success should not be exclusively attributed to purely rational actions, such as raising awareness or showing the benefits of the technique. Paradoxically, the posture of the reiki followers can create obstacles for the diffusion of the therapy in hospital environment, so that the diffusion is a creative action that requires adaptations and transformations of the technique itself to deal with unforeseen situations of the new context. To conclude, two parallel movements were observed, starting from the work activity of the followers to reiki care, which can guide other ventures to achieve a better hospital diffusion. The first concerns the transition from the "mystical reikian" to the reikian who presents himself in a more neutral and standardized way; and the second, in the sense of delineating the identity of reiki, which goes from "good for everyone at any time" to a complementary therapy and consistent with the treatment of the specialties already existing in the hospital.